URBAN VILLAGE LITERACY: DELVING ITS PROFOUND IMPLEMENTATION AND OBSTACLES - Maharani, Anak Agung Putri (Jurnal Pendidikan Bahasa Inggris Indonesia, 2020)
School Literacy Movement (henceforth, SLM) is a pivotal program which published to deal with students? problem in literacy skills. Due to its crucial role, its implementation needs to be evaluated in the attempt to enrich the quality of the program. Therefore, this mini research was conducted involving two primary schools in Sempidi urban village to answer two research objectives; to explore the process of School Literacy Movement in Sempidi urban village primary schools and to figure out the obstacles found while implementing School Literacy Movement implemented in Sempidi urban village primary schools. To garner a rich set of data, 4 respondents (2 principals and 2 teachers) were invited to join this mini research. Additionally, to collect data, the method of data collection was observation, interview and Focus Group Discussion (hereafter, FGD). It was found that literacy skills in each school focus on different stages of SLM as well as different reading activities assigned for the students. Another finding was the obstacles faced during the implementation of SLM are originally from the teachers, the students, and the facilities that support the literacy.